Identification Of A Small Man-Made Marine Placer - Caleen E. Kilby (International Marine Minerals Society, 1994)
A program of surveying and studying the surficial sediments of northern Juan de Fuca Strait was undertaken between 1988 and 199 1. Detrital sediments were mapped from the intertidal zone down to 100 m depth along the slopes of a series of shallow coastal marine terraces. The sand heavy mineral content was examined over this region and sediment geochemistry and assays were performed on selected samples both offshore and from beaches along the coast. The coastline of southwestern Vancouver Island has numerous streams, with a history of small Au placer extraction, which empty into the strait to the south. Only very minor evidence of this was seen in values from isolated locales. However, one beach presented a remarkably different mineralogy and geochemistry from the remainder of the coastline. From the beach to 800 meters offshore heavy mineral contents were greatly elevated and Ti values were as high as 1.4% of the sand fraction. Minerals were relatively fresh and angular, with mineral percents distinctly different than those found elsewhere along this coastline. No stream of substantial size crosses this largely sandy-gravel beach. A series of studies identified the source of this small marine placer as having its origins n the tailings from a submarine pipe broken short in the next bay. A Cu-Au mine 1.5 km upstream, closed by the mid 1970's, had processed its ore underground and piped the crushed tailings to the submarine discharge pipe. The crushed material has been transported and concentrated with the longshore current and been sorted by strong coastal swells. Ilmenite/titanomagnetite from the homblendized basalt of the mine is the source of the Ti enrichment.